Klischee + Antiklischee : Bildformen der Gegenwart. - Becker, Wolfgang; Ludwig, Peter (Aachen : Neue Galerie im Alten Kurhaus, 1970)
Aeppli, Eva ; Alvermann, Hans Peter ; Artschwager, Richard ; Baer, Joe ; Brüning, Peter ; Bubenik, Gernot ; Castro, Lourdes ; Christo ; Close, Chuck ; Cote, Alan ; D'Arcangelo, Allan ; Deem, George ; Dienst, Rolf-Gunter ; Dubuffet, Jean ; Errò ; Fangor, Wojciech ; Gaul, Winfred ; Gilardi, Piero ; Gnoli, Domenico ; Graham, Robert ; Graves, Nancy Stevenson ; Graziani, Sante ; Guttuso, Renato ; Hanson, Duane ; Hockney, David ; Indiana, Robert ; Johns, Jasper ; Jones, Allen ; Kanovitz, Howard ; Kelly, Ellsworth ; Klapheck, Konrad ; Kolar, Jiri ; Lichtenstein, Roy ; Lozano, Lee ; Nauman, Bruce ; Nesbitt, Lowell ; Neuenhausen, Siegfried ; Oldenburg, Claes ; Pascali, Pino ; Pavlos (Pavlos Dionyssopoulos) ; Ramos, Mel ; Rauschenberg, Robert ; Richter, Gerhard ; Roth, Dieter ; Segal, George ; Smith, Leon Polk ; Smithson, Robert ; Stafford, Lawrence ; Stein, Lewis ; Stenvert, Curt ; Tilson, Joe ; Twombly, Cy ; Uecker, Günther ; Vostell, Wolf ; Warhol, Andy ; Watts, Robert ; Wesselmann, Tom ; Wewerka, Stefan ; Wintersberger, Lambert Maria ; Young, Peter
Klischee + Antiklischee : Bildformen der Gegenwart, Neue Galerie im Alten Kurhaus, Aachen, Februar 1970
biografie
Duits
boek